Faktor-Faktor Yang Mempengaruhi Kinerja Dewan Perwakilan Rakyat Daerah Dengan Kompensasi Sebagai Variabel Moderating - Amrizal Achmad; Belli Nasution; Muchid Muchid (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The main problem in this study is how the influence of self-potential, learning motivation, social environment, and job prospects on the student's decision to choose to study at the Arabic Language Study Program of UIN Sultan Maulana Hasanuddin Banten. Several hypotheses have been determined in this study to answer these hypotheses using quantitative methods. The instrument testing includes the validity test, reliability test, and classical assumption test, and finally the hypothesis test (T test). The results showed that there were two research hypotheses (H1 and H3) where the results showed that the proposed research hypothesis was rejected, the namely self-potential and social environment had no significant effect on the decision to choose to study at the BSA UIN SMH Banten Study Program. Then, it was found that the other hypotheses (H2 and H4), namely motivation variables and job prospects, were stated to have a significant effect on the decision to choose a college at the BSA Study Program UIN SMH Banten. Keywords : Self-Potential, Learning Motivation, Social Environment, And Job Prospects, Student's Decision